Adoção das práticas de testes do modelo CMMI na melhoria da qualidade dos produtos e serviços de testes de software em instituições financeiras - Dias, Roni Queiroz (2005)
This research intends to identify the impacts of product quality and software testing services with the use of practices based in process areas of Verification and Validation of the model CMMI(Capability Maturity Model Integration) in banking organizations. Inside this context, such research has searched for indentifing through 40 products that were tested by a supplier the level of tack to such practices. After this analise, it was noticed together with the client using questionnaires of the avaliation models of software quality ISO/IEC 9126 and service quality SERVQUAL and its respectively impacts in quality. The theorical references used are Software Testing, ISO/IEC 9126, the CMMI (Capability Maturity Model Integration) of SEI (Software Engineering Institute), of the Carnegie Mellon University and (SERVQUAL) from Valerie A. Zeithaml, A. Parasuraman and Leonard L. Berry